Complex Ballot Propositions, Individual Voting Behavior, and Status quo Bias - Zohal Hessami; Sven Resnjanskij (Center for Economic Studies and ifo Institute (CESifo), 2018)
One concern about direct democracy is that citizens may not be sufficiently competent to decide about complex policies. This may lead to exaggerated conservatism in the voting decision (status quo bias). To investigate how complexity affects individual voting behavior, we develop a novel measure of proposition complexity (using official pre-referendum booklets) and combine it with post-referendum survey data from Switzerland. Using Heckman selection estimations to account for endogenous variation in participation rates, we find that an increase in proposition complexity from the 10th to the 90th percentile would decrease voters' approval by 5.6 ppts, which is often decisive: an additional 12% of the propositions in our sample would be rejected.
Keywords: D72; D78; 330; voting behavior; proposition complexity; direct democracy; status quo bias; Heckman probit model